GRAVITY EFFECT ON WELL SCREEN ALIGNMENT DURING THE IN-SITU LEACHING - Shayakhmetov, N.M.; Kurmanseiit, M.B.; Alibayeva, K.A. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The production of a mineral via in-situ leaching method in the conditions of a rollfront deposit is accompanied by many problems associated with the impossibility of direct observation of the process. This article discusses the problem of the influence of the density heterogeneity of the injected solution on the efficiency of well screen operation. As a result of the influence of gravitational forces, with a non-uniform distribution of the density of the liquid, the effect of a "fall" of solutions occurs, which significantly reduces the efficiency of mining under conditions of well screen located at the same level and the remoteness of the lower aquiclude from the lower boundary of the well screen. The problem was investigated on the basis of mathematical modeling using finite difference schemes. The calculation was carried out for a hexagonal pattern with six injection and one production wells. The results showed that the change in the lowering level of solutions depending on the distance between the wells and the density of the injected leach solution is linear. These results make it possible to determine the effective location of well screens at various values of the density of the injected solution.